2010
DOI: 10.1186/1471-2229-10-105
|View full text |Cite
|
Sign up to set email alerts
|

Intricate environment-modulated genetic networks control isoflavone accumulation in soybean seeds

Abstract: BackgroundSoybean (Glycine max [L] Merr.) seed isoflavones have long been considered a desirable trait to target in selection programs for their contribution to human health and plant defense systems. However, attempts to modify seed isoflavone contents have not always produced the expected results because their genetic basis is polygenic and complex. Undoubtedly, the extreme variability that seed isoflavones display over environments has obscured our understanding of the genetics involved.ResultsIn this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
53
3
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 73 publications
12
53
3
2
Order By: Relevance
“…are the richest source of isoflavones (Cederroth and Nef 2009;Hollman 2001) ranging from 1.2 to 4.2 mg/kg dry matter (DM; Kurzer and Xu 1997). Isoflavone concentrations were found to vary within cultivars (Eldridge and Kwolek 1983;Hoeck et al 2000;Wang et al 2000), and their contents were fluctuating even though identical varieties were grown at different locations (Carrao-Panizzi et al 1999;Charron et al 2005;Yin and Vyn 2005) under differing climatic (Tsukamoto et al 1995) and plant stress conditions (Caldwell et al 2005;Gutierrez-Gonzalez et al 2009, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…are the richest source of isoflavones (Cederroth and Nef 2009;Hollman 2001) ranging from 1.2 to 4.2 mg/kg dry matter (DM; Kurzer and Xu 1997). Isoflavone concentrations were found to vary within cultivars (Eldridge and Kwolek 1983;Hoeck et al 2000;Wang et al 2000), and their contents were fluctuating even though identical varieties were grown at different locations (Carrao-Panizzi et al 1999;Charron et al 2005;Yin and Vyn 2005) under differing climatic (Tsukamoto et al 1995) and plant stress conditions (Caldwell et al 2005;Gutierrez-Gonzalez et al 2009, 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Another high density genetic linkage maps was constructed using the 1,536 Universal Soy Linkage Panel 1.0 SNP markers in the 'PI 438489B' by 'Hamilton' populations and 31 linkage groups were obtained and used in this study . Up to date several isoflavones QTL were identified from the linkage map constructed by different markers (Kassem et al, 2004;Gutierrez-Gonzalez et al, 2009;Zeng et al, 2009;Gutierrez-Gonzalez et al, 2010). SNP markers allow the anchoring of genetic maps and QTL on the soybean genome sequence so identifying large genomic regions each containing several hundred genes.…”
mentioning
confidence: 99%
“…Plant defense metabolites arise from the main secondary metabolic routes; i.e., the phenylpropanoid, isoprenoid, and alkaloid pathways (Gutierrez-Gonzalez et al 2010). In this study, 15 proteins (spots 47-60) were identified as being involved in the phenylpropanoid pathway (Fig.…”
Section: The Proteins Involved In the Plant Defense Signal Pathwaymentioning
confidence: 99%